Analisis Wacana Kritis Komodifikasi Daí Dalam Program Televisi - Ridwan Rustandi (Communicatus: Jurnal Ilmu komunikasi, 2018)
This study aims to determine the construction of preachers in a television broadcast. The study was conducted to answer the question of how identity construction preachers and how preachers selection criteria in propaganda programs on television. The study was conducted with a qualitative approach and methods of Critical Discourse Analysis Teun Van Dijk Models. There are three element of Critical Discourse Analysis Methods : Text, Social Cognition and Social Context. Data collection techniques used in this study is the observation, interviews, and documentation. The results showed that the commodification of propaganda on the program "Islam itu indah" made on the preacher and maudhu side. On the side of, the election preacher / resource is determined by considering certain criteria which include unification (distinguishing characteristics), tradability (popularity and publicity), skills and abilities to speak, as well as the scientific qualifications. Representation preachers on this program conducted with respect to rating and share, performance and target audience.Penelitian ini bertujuan untuk menganalisis konstruksi daí sebagai tenaga kerja dalam program televisi bertajuk “Islam Itu Indah”. Penelitian diarahkan untuk menggali aspek komodifikasi yang berkaitan dengan kriteria pemilihan dai’dan konstruksi daí dalam program televisi. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis wacana kritis (Critical Discourse Analysis) model Teun Van Dijk. Terdapat tiga elemen dalam Analisis Wacana Kritis Teun Van Dijk, yaitu teks, kognisi sosial dan konteks sosial. Teknik pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa komodifikasi dakwah pada program “Islam Itu Indah” dilakukan pada sisi da’i dan maudhu. Pada sisi da’i, pemiihan da’i/narasumber ditentukan dengan mempertimbangkan kriteria tertentu yang meliputi unifikasi (karakter pembeda), daya jual (popularitas dan publisitas), keterampilan dan kecakapan berbicara, serta kualifikasi keilmuan. Representasi da’i pada program ini dilakukan dengan memperhatikan rating and share, performa dan sasaran audiens.